Voids in materials : from unavoidable defects to designed cellular materials - Gladysz, Gary M. (Oxford, England ; Waltham, Massachusetts : Elsevier, 2015)
Voids in Materials treats voids of different shapes and forms in various materials, and examines their effects on material properties. The book covers the origins of voids in materials, how they are sometimes introduced in the form of hollow spheres, and the resultant properties of materials containing voids. There are many books that focus on foams (which intentionally incorporate voids into materials) and that cover voids incidental to or unwanted in the fabrication of non-porous materials. In fact, all materials have voids. This book starts from the premise that voids are pervasive in all material on some level. It goes beyond foams to provide a comprehensive overview of voids, a central reference for scientists and engineers to use for the effect of voids in materials.
Includes bibliographical references at the end of each chapters and indexes.
Description based on online resource; title from PDF title page (ebrary, viewed September 19, 2014).
Elsevier
Keywords: Materials -- Analysis; Strength of materials; Materials; Materials; Materials -- Analysis; Strength of materials; Electronic books